Ստրուկ–զինվորականության ծագման ակունքների որոշ ասպեկտների շուրջ - Միքայելյան, Տիգրան («Զանգակ - 97»)
Among the factors which supported the introduction of military-slavery (ghulam-mamluk) institution by Abbasid caliph Mu'tasim in the first third of IX c. the following should be mentioned. We also suggest that Byzantine Emperor's tradition of recruitment troops of alien origin may have also influenced on the establishment of ghulam army by the Abbasids. However this problem needs further investigation. To summarise one can stress that two last factors may have nad particular importance in adoption of slavery military institution by Abbasids.
Keywords: Պատմություն